High plasma concentrations of asymmetric dimethylarginine inhibit ischemic cardioprotection in hypercholesterolemic rats - Landim,M.B.P. (2013)
A low concentration of nitric oxide associated with a high concentration of asymmetric dimethylarginine (ADMA) can explain the lack of ischemic cardioprotection observed in the presence of hypercholesterolemia. The objective of the present study was to evaluate the effect of hypercholesterolemia on ischemic pre- and postconditioning and its correlation with plasma concentrations of ADMA. Male Wistar rats (6-8 weeks old) fed a 2% cholesterol diet (n = 21) for 8 weeks were compared to controls (n = 25) and were subjected to experimental myocardial infarction and reperfusion, with ischemic pre- and postconditioning. Total cholesterol and ADMA were measured in plasma before the experimental infarct and the infarct area was quantified. Weight, total cholesterol and plasma ADMA (means ± SE; 1.20 ± 0.06, 1.27 ± 0.08 and 1.20 ± 0.08 vs0.97 ± 0.04, 0.93 ± 0.05 and 0.97 ± 0.04 µM) were higher in animals on the hypercholesterolemic diet than in controls, respectively. Cardioprotection did not reduce infarct size in the hypercholesterolemic animals (pre: 13.55% and post: 8% compared to 7.95% observed in the group subjected only to ischemia and reperfusion), whereas infarct size was reduced in the animals on a normocholesterolemic diet (pre: 8.25% and post: 6.10% compared to 12.31%). Hypercholesterolemia elevated ADMA and eliminated the cardioprotective effects of ischemic pre- and postconditioning in rats.